PERBANDINGAN DAYA DUKUNG AKSIAL PONDASI BORED PILE BERDASARKAN METODE EMPIRIS DAN PEMODELAN SOFTWARE (STUDI KASUS: PROYEK JEMBATAN KUTOREJO) - Dina Kurnia Shanty; Akhmad Wildan Mukhollad; Himatul Farichah (LPPM Universitas Abdurrab, 2026)
Bridges are a critical component of infrastructure, facilitating connectivity between distinct regions and necessitating robust foundational structures to endure traffic loads and environmental conditions. The Kutorejo Bridge construction project employed bored pile foundations, selected for their capacity to support substantial loads with minimal vibration during construction. This study seeks to compare the axial bearing capacity of bored pile foundations utilizing the empirical method of L. Decourt (1996) and Geo5 numerical modeling. The analysis concentrates on the axial bearing capacity of a single pile through a quantitative approach and a comparative-descriptive method. Secondary data were derived from the Standard Penetration Test (SPT) results at two bore hole locations (BH-1 and BH-2), encompassing N-SPT values, soil types, and foundation dimensions. The calculation results indicated that the allowable bearing capacity calculated using the L. Decourt method was higher than the results from Geo5 modeling, with values of 3375,5 kN at BH-1 and 4019,8 kN at BH-2, compared to 2209 kN and 3163,9 kN from Geo5, respectively. This difference corresponds to an average discrepancy of 27.3%. Despite the variance in results, both methods yielded bearing capacity values exceeding the planned axial load of 1305,868 kN, thereby affirming the foundation's safety.